2021
DOI: 10.1186/s12879-020-05730-z
|View full text |Cite
|
Sign up to set email alerts
|

JAK-inhibitor and type I interferon ability to produce favorable clinical outcomes in COVID-19 patients: a systematic review and meta-analysis

Abstract: Background The spread of a highly pathogenic, novel coronavirus (SARS-CoV-2) has emerged as a once-in-a-century pandemic, having already infected over 63 million people worldwide. Novel therapies are urgently needed. Janus kinase-inhibitors and Type I interferons have emerged as potential antiviral candidates for COVID-19 patients due to their proven efficacy against diseases with excessive cytokine release and their direct antiviral ability against viruses including coronaviruses, respectively… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 43 publications
4
41
0
1
Order By: Relevance
“…A systematic review and meta-analysis have been previously performed to evaluate the effects of IFN-I and Janus Kinaseinhibitors as treatments for COVID-19 patients and their effectiveness to produce positive outcomes (56). They found that IFN-I treatment is associated with positive clinical outcomes regarding mortality and discharge (56). The time to start IFN-I treatment might be crucial (57).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review and meta-analysis have been previously performed to evaluate the effects of IFN-I and Janus Kinaseinhibitors as treatments for COVID-19 patients and their effectiveness to produce positive outcomes (56). They found that IFN-I treatment is associated with positive clinical outcomes regarding mortality and discharge (56). The time to start IFN-I treatment might be crucial (57).…”
Section: Introductionmentioning
confidence: 99%
“…In a descriptive review of literature about the role of IFN-I in treating COVID-19, it is highlighted that IFN-α use at the early phase of COVID-19 presents a positive outcome, but IFN-β-1a and -1b are more effective to hinder COVID-19 ( 55 ). A systematic review and meta-analysis have been previously performed to evaluate the effects of IFN-I and Janus Kinase-inhibitors as treatments for COVID-19 patients and their effectiveness to produce positive outcomes ( 56 ). They found that IFN-I treatment is associated with positive clinical outcomes regarding mortality and discharge ( 56 ).…”
Section: Introductionmentioning
confidence: 99%
“…For critical condition, tocilizumab, a recombinant monoclonal immunoglobulin G1, also showed satisfactory effect against the infection [85]. Interferon alpha and Janus-kinase inhibitor are also recommended, as they showed a significant decrease in SARS-CoV-2 virus replication [86], mortality rate and ICU admission of COVID-19 patients [87]. Convalescent plasma transfusion might also be a promising treatment against COVID-19 as its use reduces mortality in critically ill patients increasing neutralizing antibody titers and decreasing SARS-CoV-2 viral RNA [88,89].…”
Section: 4present Containment Strategies Of All Outbreaksmentioning
confidence: 99%
“…Most dramatically, more than 70% of morality rate bearing black fungus have no effective treatment except antifungal, antibiotics, intravenous (IV) medication or through a surgery [87]. Importantly, utilizing its experience of Ebola outbreak, Democratic Republic of Congo has established a multisectoral public health approach for community based screening testing, contact tracing, risk communication, community engagement and case management to fight against COVID-19 and other deadly super contagious pathogens [51].…”
Section: 4present Containment Strategies Of All Outbreaksmentioning
confidence: 99%
“…The potential of IFN-1 as a treatment for viral respiratory infections is strongly suggested by the limited IFN-1 responses of SARS-CoV-2-infected patients (3,4). The COVID-19 experience demonstrated that patients with SARS-CoV-2 are both (a) very susceptible to IFN-I and (b) uniquely adept at evading endogenous IFN-I by delaying or suppressing IFN-I expression (3)(4)(5)(6)(7). The ability of SARS-CoV-2 to inhibit endogenous IFN-I expression appears to make interferon pathway dysregulation critical to developing severe disease (5).…”
Section: Introductionmentioning
confidence: 99%